A „távollétes ügyek” egyes elméleti és gyakorlati kérdései a büntetőeljárásban - Tarr, Ágnes (Debreceni Jogi Műhely, 2005)
The idea of simplification of the law of criminal procedure has been an interesting topic in the science of law for a long time. Practical necessities, namely the overburdening of the criminal courts and the new challenges of the criminal law called this concept into life. Finishing up a procedure in a reasonable time limit is a very crucial interest – as it was pointed out several times by the Council of Europe, Committee of Ministers and also the Hungarian Constitutional Court. As the international principle declared in the Human Rights says everyone has the right to plead its case within a reasonable period and it can only be achieved that way.Because of the reasonable time limit required for a procedure, various simplifications of methods have been introduced into the national systems of criminal procedure. As a part of this process several legal institutions were introduced in the Hungarian law system aiming to accelerate the legal procedure. One of them, which is called special procedure against absent accused, is regulated by Chapter XXIV. of the Law of Criminal Procedure.This essay deals with this special procedure in details. Firstly I show through a short international outlook how the procedure against absent accused appears in the practice of the European Council and the European Union. Hereafter a certain case is examined in details where the European Court for Human Rights considered the necessity of the accused person’s appearance. The Court established a principle if the absence of the accused had hurt the requirements of the fair trial. According to this the appearance of the accused person is necessary if it could play a role in the forming of the Court’s opinion.Next, I examine the problems connected to the Hungarian regulations because recently serious constitutional worries have appeared related to this legal institution. As a result of this the Constitutional Court made its decision (n. 14/2004) and found many paragraphs of the then existing legal institution unconstitutional. Based on this Decision I go through in details all the problems and requirements related to this procedure. In the light of this, the regulation effective from the 1st of January, 2005 is described, which – according to my opinion – meets the requirements made by the Constitutional Court, so it is exceptional and provisional.In the next chapter certain practical experiences of the procedure against absent accused are examined. Here it is stated that the application of this legal institution is the rarest among the legal institutions aiming the acceleration of legal procedures. I explain it by the fact that this is a relatively young legal institution and there was not enough time since it was introduced to give certain conclusions, moreover the application is limited concerning the range of individuals. As a conclusion it can be stated that the application is more common in those cases where the accused is abroad but does not stay in an unknown place. I call the attention to some problems emerged in the practice as the protection of the accused, or the delivery of the copy of indictment and summons, etc.As a final conclusion it can be stated that using this legal institution is not so common but the importance of this will increase in the future by joining to the EU because of the easier way of crossing the boards. Hopefully the regulation, which suits to the requirements of the Constitutional Court, will be proper to gain its original aim, namely to simplify and accelerate the legal procedure.